Artificial Protein Coronas Enable Controlled Interaction with Corneal Epithelial Cells: New Opportunities for Ocular Drug Delivery - Carlo Astarita; Sara Palchetti; Mina Massaro-Giordano; Marina Di Domenico; Francesco Petrillo; Silvia Boffo; Giulio Caracciolo; Antonio Giordano (MDPI AG, 2021)
Topical administration is the most convenient route for ocular drug delivery, but only a minor fraction is retained in the precorneal pocket. To overcome this limitation, numerous drug delivery systems (DDS) have been developed. The protein corona (PC) is the layer of biomolecules (e.g., proteins, sugars, lipids, etc.) that forms around DDS in physiological environments by non-covalent interaction. The PC changes the DDS physical-chemical properties, providing them with a completely novel biological identity. The specific involvement of PC in ocular drug delivery has not been addressed so far. To fulfill this gap, here we explored the interaction between a library of four cationic liposome-DNA complexes (lipoplexes) and mucin (MUC), one of the main components of the tear film. We demonstrate that MUC binds to the lipoplex surface shifting both their size and surface charge and reducing their absorption by primary corneal epithelial cells. To surpass such restrictions, we coated lipoplexes with two different artificial PCs made of Fibronectin (FBN) and Val-Gly-Asp (VGA) tripeptide that are recognized by receptors expressed on the ocular surface. Both these functionalizations remarkedly boosted internalization in corneal epithelial cells with respect to pristine (i.e., uncoated) lipoplexes. This opens the gateway for the exploitation of artificial protein corona in targeted ocular delivery, which will significantly influence the development of novel nanomaterials.